Answer:
Only equation 1 and 2 are equal.
Step-by-step explanation:
2 (x + 4)2 = 2
2( x² + 8x+ 16) = 2 Applying the square formula
2x² + 16x+ 32 = 2
2x² + 16x+ 32 -2= 0
2x² + 16x+ 30 = 0
2( x² + 8x+ 15)= 0 Taking 2 as common
x2 + 8x + 15 = 0------------eq 1
x2 + 8x + 15 = 0-------------eq 2
(x − 5)2 = 1
x²-10x+25= 1 Applying the square formula
x²-10x+25- 1= 0
x²-10x+24= 0-------------eq 3
x2 − 10x + 26 = 0 -------------eq 4
3(x − 1)2 + 5 = 0
3( x²-2x+1)+5= 0 Applying the square formula
3x²-6x+3+5= 0
3x²-6x+ 8= 0-------------eq 5
3x2 − 6x + 8 =1
3x2 − 6x + 8 -1=0
3x2 − 6x + 7 =0-------------eq 6
4.5X+1450=C
X represents the amount of square feet
C represents the total cost
Step-by-step explanation:
a. x = 30° (180-70-80)
b. <FGA = 80°
c. vertical angles
Yes because the zero has no value.
I believe it would be $4,399.15 because if you use the formula I=P*R*T
P=62,845
R=0.07 or 7%
T=1 year period
So overall your equation is 62845*0.07*1=$4,399.15
Now at this point the interest is added onto the principal amount to figure out some new amount after one year so:
62845.00+4399.15=$67,244.15